SOSIALISASI ANAK DALAM MASYARAKAT DI KELURAHAN AIRTIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Wirdatul Janna; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This thesis put forward in order to achieve a degree qualified strata 1 (S1) Sociology.By title “SOCIALIZATION OF CHILDREN IN VILLGE COMUNITIES AIRTIRIS DISTRICTS KAMPAR DISTRICT KAMPAR ”. Kelurahan Airtiris have a tradition that still survive, namely Tradition nujuh Monthly, Aqikah, Down Bath and Khitanan. But over the development period of this tradition began less done or made in whole the like where appropriate. Issues raised in this issue is 1. What are the values inherited in the child socialization patterns during pregnancy after givibirth and adolescence, 2. How do rite performed in the process of socialization of children in the community pattern Airtiris Kampar Kampar Regency. The method used is qualitative research methods. The research location in the village Airtiris Kampar Kampar District. That is the subject of this research is the community of parents who have children. Keywords: Tradition Society Airtiris, children in villge, Airtiris